Types of perceived social support and dimensions of the hardiness trait: A multivariate regression analysis - Thuy Dang; Fatmanur Çifci (International Journal of Personality Psychology)
While existing research has explored the buffering effects of social support and hardiness separately, there is a gap in understanding their interrelationship within the college student population. This study aimed to explore which dimensions of the hardiness trait (capturing commitment, control, and challenge) are associated with which types of perceived social support (attachment, guidance, social integration, reliable alliance, reassurance of worth) among college students. This study thus will contribute to the social support and hardiness literature by providing empirical evidence on how these constructs are specifically related to each other, offering insights that can inform future research, interventions, and practice. The data for this study were obtained from Dang’s (2024) doctoral dissertation examining the relation between social support, distress tolerance, and self-regulated learning. The participants were 323 full-time students (59% male, Mage = 28.3). Multivariate regression analyses were conducted in R to assess the relations between subscales of hardiness and types of perceived social support. Social support turned out to be positively related to commitment and control dimensions of hardiness and was negatively related to the challenge dimension of hardiness. The results of further analysis indicated that perceiving attachment support and guidance support were associated with the control dimension of the hardiness trait.